2015
DOI: 10.1111/jan.12866
|View full text |Cite
|
Sign up to set email alerts
|

Sex life and role identity in Taiwanese women during menopause: a qualitative study

Abstract: Given the variety of reactions to the impact of menopause on sexual behaviour/relationships seen here, it is clear that health professionals need to assess of each woman's specific situation and be prepared to recommend a variety of behavioural or hormonal treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 50 publications
0
14
0
3
Order By: Relevance
“…The available information on quality of sexual life in the literature is scarce. Our study adds new evidence that suggests that respondents with female sexual dysfunction have poorer sexual health- (Ling, Wong, & Ho, 2008;Yang, Kenney, Chang, & Chang, 2016 cally, these women allowed their spouse to find other women to satisfy their sexual desires (Liu & Eden, 2007).…”
Section: (Informant 8)mentioning
confidence: 69%
See 2 more Smart Citations
“…The available information on quality of sexual life in the literature is scarce. Our study adds new evidence that suggests that respondents with female sexual dysfunction have poorer sexual health- (Ling, Wong, & Ho, 2008;Yang, Kenney, Chang, & Chang, 2016 cally, these women allowed their spouse to find other women to satisfy their sexual desires (Liu & Eden, 2007).…”
Section: (Informant 8)mentioning
confidence: 69%
“…& Ling et al. in Taiwan and China (Ling, Wong, & Ho, ; Yang, Kenney, Chang, & Chang, ). Sexual disharmony was viewed as an important cause of marital strife.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Personality development (seeking to advance empowerment) and self-retrieval depend on the level of coordination with circumstances and active coping with menopause was consistent with domination over the environment, as proposed in Ryff's model. Accepting the status quo, accepting the changes caused by menopause and incorporating menopause into one's identity were the necessary conditions for adopting appropriate strategies for managing menopause in Taiwanese women (Yang, Kenney, Chang, & Chang, 2016). The participants of the present study incorporated menopause into their identity by accepting it and using practical solutions.…”
Section: Discussionmentioning
confidence: 93%
“…This indicates that the participants put their (male) partner's sexual needs first, and can be read as a way of managing an interpersonal relationship in the context of experiencing a sexual difficulty and not knowing how else to manage it. Indeed, Yang et al (2016) found that heterosexual Taiwanese women of menopause age felt guilt and frustration over the perceived impact of their sexual difficulty for their husbands which created a pressure to have intercourse. Ussher, Perz and Parton (2015, p.454) reported that heterosexual women at menopause with no desire for sex engaged in it because 'they and their partners viewed coital sex as important to their relationship'.…”
Section: Discussionmentioning
confidence: 99%